Uji Daya Hambat Daun Salam Koja (Murraya koenigii (L.) Spreng) terhadap Pertumbuhan Bakteri Escherichia Coli dan Staphylococcus Aureus dengan Metode Kirby Bauer - Eny Purwanitiningsih; Nurbaiti; Arum Lintang D.L (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Salam Koja (Murraya koenigii) is a species belonging Rutaceae that contains active antibacterial compounds. These leaves can be used to kill or inhibit the growth of pathogenic bacteria in humans, namely Escherichia coli and Staphylococcus aureus. This study aims to determine the ability of koja bay leaves to inhibit the growth of Escherichia coli and Staphylococcus aureus bacteria, and to determine the concentration of koja bay leaves which is the most effective in inhibiting the growth of E. coli and S.aureus. This study used the Kirby Bauer diffusion method with 5 treatments and 5 replications. The concentrations tested were 0%, 25%, 50%, 75%, and 100%. Data analysis used one-way ANOVA test. Koja bay leaves (Murraya koenigii) can inhibit the growth of Escherichia coli and Staphylococcus aureus which is characterized by the formation of a clear zone. The 25% concentration of Salam Koja leaves (M. koenigii) has been effective in inhibiting the growth of Escherichia coli and Staphylococcus aureus bacteria. This proves that koja bay leaves contain active compounds that are antibacterial, such as alkaloids, flavonoids, tannins, saponins, terpenoids, steroids, and essential oils.